PERLINDUNGAN HAK-HAK PEREMPUAN PASCA PERCERAIAN (STUDI TERHADAP PUTUSAN PENGADILAN AGAMA PALOPO) - Marwing, Anita (Lembaga Penelitian dan Pengabdian pada Masyarakat (LP2M) IAIN Palopo, 2016)
This article aims to determine the women rights in Islam, in post-divorces and in knowing the analysis of judgesâ decision in Palopo Religious Court regarding the women rights after divorcing. The findings showed that the judges decision regarding the rights of women were concluded as follows; 1) the contested or talak divorce cases by verdict judgment did not cover the wives rights in which judges presumption should not decide the case on the outside of the charge materials (ultra-petition). So that, the judge did not have the courage to assign or guarantee legally the women rights after divorcing such as Muta, child custody, property rights if not being the charge materials. 2) The contested divorce cases did not cover any lawsuit regarding the wives rights. Although the judge had the ex officio rights in determining the wives rights whether requested or not, the judges of Palopo Religious Court were just in case of the cause of divorce where the husband and wife were not willing to be divorced. So, the judges utilized their ex officio rights to punish the husbands for providing Muta according to their ability and feasibility. 3) In reconvenes decision, it was clearly mentioned the wives rights in the judgesâ decision in which they are Iddah living, Mutah, past living, and the child costs. At the living Iddah costs, it was decided by Palopo Religious Courts Palopo that it is not in the same nominal amount. It is also similar with the Mutah and children costs.